Live Music Performance: The Relationship Between Flow and Music Performance Anxiety - Spahn, Claudia; Krampe, Franziska; Nusseck, Manfred (Frontiers in Psychology, 2021)
Most studies exploring the relation between flow and Music Performance Anxiety (MPA) have focused on the disposition of generally experiencing flow and the occurrence of MPA. Little is known about the connection between experiencing flow and MPA as it relates to a specific performance. In this study, flow and MPA have been investigated in 363 orchestral musicians in relation to a particular live music performance. The musicians were asked to fill out a questionnaire immediately after a concert. Flow experience during the performance was measured using the Flow Short Scale of Rheinberg, Vollmeyer and Engeser (2003). The Performance-specific Questionnaire on MPA (PQM, Spahn et al., 2016) was used for MPA. The PQM addresses particular aspects of MPA and refers retrospectively to the time before and during the performance as well as to the moment of filling out the questionnaire after the performance. Using three scales, the functional coping, the perceived symptoms of MPA and self-efficacy were determined for each time point of the performance. The results showed that experiencing flow was on average higher among orchestral musicians compared to a sample of the general population. However, there were differences between the professional and non-professional musicians. All PQM scales showed significant correlations with the global flow scale. Regression analysis on the global flow score found that regarding the time before the performance the PQM scale symptoms of MPA were diametrically connected with the flow experience. The PQM scale functional coping was shown to be positively related to the flow during the performance. Moreover, high self-efficacy was found to be closely related with stronger flow experience. Furthermore, flow seems to have positive effects on functionally coping with MPA and the self-efficacy after the performance. These findings confirm the negative relationship between flow and symptoms of MPA, offering further approaches in understanding the relationship especially for live music performances.